TRADISI MATITISUARA PADA NGUSABA KEDASA DI PURA ULUN DANU BATUR DESA BATUR KECAMATAN KINTAMANI KABUPATÉN BANGLI (KAJIAN BAHASA BALI): (Kajian Bahasa Bali) - Jutama, I Nengah Eris; Ekawati, Relin Denayu; Nerawati, Ni Gusti Ayu Agung; Sena, I Gusti Made Widya; Putrawan, I Nyoman Alit (Sphatika: Jurnal Teologi, 2026)
This research analyzes the Matitisuara Tradition performed during the Ngusaba Kedasa ceremony at Ulun Danu Batur Temple, Batur Traditional Village, Kintamani, Bangli. The primary focus is to examine the lingual forms of the Balinese language within the tradition, its role in the community, and its implications for the mindset of local residents. This study employs a qualitative method with a descriptive approach. Data were collected through participant observation, in-depth interviews with key informants such as Dané Jero Penyarikan and traditional leaders, and document studies of the Raja Purana of Ulun Danu Batur Temple. Data analysis was conducted inductively, involving data reduction, data display, and conclusion drawing based on structuralism, sociolinguistics, and functionalism theories. The results indicate that from a microlinguistic perspective, the Matitisuara tradition preserves the unique characteristics of the Batur dialect, such as the distinct pronunciation of the vowel phoneme /a/ at the end of words. Macrolinguistically, this tradition functions as a spiritual communication medium containing essential wisdom (piteket) for the community's social and economic life. There are three main verses of wisdom emphasizing the importance of hard work (daak), persistence in endeavors even when starting small, and the wise use of funds for social and religious investment. The implications of this tradition are profound, as Matitisuara serves as an ethical foundation and motivation for various professions, including teachers, farmers, and undagi (traditional builders), in performing their duties with dedication and devotion. In conclusion, the Matitisuara Tradition is not merely a religious ritual but a vital instrument for internalizing noble values and strengthening cultural identity, maintaining harmony within the Batur Village community.